Associate Law For Functions Compose
Feb 22, 2023
The derivation process for functions compose
The introduction for functions compose is here.
Definition : Functions Compose
compose = (funa, funb) => (c) => funa(funb(c));
Now we are supposed to give the proof and derivation process of the following conclusions
Associate Law For Functions Compose
compose((funa, funb), func)) = compose(funa, (funb, func))
It's simple to prove this proposition with the definition of functions compose.
according to
compose(a, b) = (D) => a(b(D));
We assign the argument b
with
b = compose(x, y);
So we get
compose(a, b) = compose(a, compose(x, y))
= (D) => a(compose(x, y))
= (D) => a(x(y(D)))
We find that
(D) => a(x(y(D)))
= (D) => compose(compose(a,x),y)
So we have the conclusion
compose(compose(a, x), y) = compose(a,compose(x, y));
QED.
We logically have the expanded conclusion: If there are n function combinations
The proof of this proposition is omitted.